2001
DOI: 10.1161/hq0701.092136
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Wall Mechanics and Composition in a Transgenic Mouse Model of Marfan Syndrome

Abstract: Abstract-In Marfan syndrome, mutations of the fibrillin gene (FBN1) lead to aneurysm of the thoracic aorta, making the aortic wall more susceptible to dissection, but the precise sequence of events underlying aneurysm formation is unknown. We used a rodent model of Marfan syndrome, the mgR/mgR mouse (with mgR: hypomorphic FBN1 mutation), which underexpresses FBN1, to distinguish between a defect in the early formation of elastic fibers and the later disruption of elastic fibers. The content of desmosine plus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 20 publications
11
89
0
Order By: Relevance
“…5 The importance of medial elastic fibers in preserving aortic elasticity has been clearly demonstrated in both animal and human studies. 19, 20 Thus, aortic wall stiffness measured by PWV may be useful as a surrogate marker of aortic medial pathology in patients with SiV.…”
Section: Discussionmentioning
confidence: 99%
“…5 The importance of medial elastic fibers in preserving aortic elasticity has been clearly demonstrated in both animal and human studies. 19, 20 Thus, aortic wall stiffness measured by PWV may be useful as a surrogate marker of aortic medial pathology in patients with SiV.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic wall pathogenesis among the CTDs is similar, and includes fragmentation of elastic fibers and collagen deposition, 5 leading to aortic stiffness. 6, 7 Nollen et al demonstrated that aortic stiffness could also be an independent predictor of progressive aortic dilatation in adult MFS patients. 8 Increased aortic stiffness has been reported in children and adults with MFS, LDS, and other CTDs.…”
Section: Subjectsmentioning
confidence: 99%
“…43 Electron microscopy showed that elastic laminae had an unusually smooth surface and lacked the cell attachments normally mediated by FBN1. 44 Bunton et al 44 suggested that the loss of cell attachments triggers signaling initiating a nonproductive program for the synthesis and remodeling of an elastic matrix.…”
Section: Marfan Syndromementioning
confidence: 99%